Vascular remodelling in malignant hypertension - Collidge, Tara (The University of Edinburgh, 2006)
The incidence of malignant hypertension (MH) fails to decline. Improved anti¬ hypertensive agents have reduced mortality, but the economic burden remains high due to complications such as end stage renal failure. Since the condition is initially asymptomatic, little is known about early pathogenesis. However the principal pathology is vascular remodelling of resistance vessels, termed fibrinoid necrosis, which causes ischaemic end-organ injury. Cardiovascular disease is the leading cause of mortality in western society and typically the consequence of atheromatous and/or hypertensive remodelling. As such, attention has focused on understanding the processes that contribute to various forms of vascular remodelling.

It is apparent that inflammation plays an important role in modulating, and possibly initiating, some types of large vessel disease including atheroma. Less is known regarding hypertensive remodelling of resistance vessels.

Recently a highly controllable and reproducible animal model of MH was developed in the rat. The Inducible Hypertensive Rat (IHR) exploits conditional transgenic technology allowing renin expression to be switched on, and hypertension to develop, following exposure to a dietary inducing agent. The resulting phenotype resembles human MH, where inappropriate activation of the renin angiotensin system is also seen.

This study used the IHR to characterise the development of MH with specific reference to the renal vasculature. Histological injury and hypertension were pre-dated 1 by adventitial fibroblast proliferation and inflammatory cell infiltration. In order to determine the role of inflammatory cells the immunosuppressant FK506 was administered pre-emptively, resulting in the total abolition of hypertension and endorgan injury.

To allow further investigation of inflammation, the MH phenotype was developed in mice using subcutaneous angiotensin II infusion. When MH was superimposed on a transgenic line susceptible to conditional macrophage depletion, vascular remodelling failed to occur in the mesenteric circulation where depletion was greatest.

The effect of volume expansion on the IHR was assessed. Transgenic animals craved saline and the resulting fluid overload overcame cerebral autoregulation resulting in ischaemic stroke without alteration in systemic hypertension or pathology. The onset of stroke was tightly predictable and reproducible. Accordingly, the salineloaded IHR represents a novel and inducible model of ischaemic stroke.

In conclusion, this study has identified inflammation as an early and important event in the pathogenesis of MH in two rodent models. Additionally, cerebral autoregulation in the IHR could be overcome by fluid overload resulting in the dissociation of central and systemic pathology.